2022
DOI: 10.3389/fphar.2021.752244
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Allicin on Acute Myocardial Infarction in Rats via Hydrogen Sulfide-mediated Regulation of Coronary Arterial Vasomotor Function and Myocardial Calcium Transport

Abstract: Acute myocardial infarction (AMI) is a condition with high morbidity and mortality, for which effective treatments are lacking. Allicin has been reported to exert therapeutic effects on AMI, but the underlying mechanisms of its action have not been fully elucidated. To investigate this, a rat model of AMI was generated by ligating the left anterior descending branch of the coronary artery. DL-propargylglycine (PAG), a specific hydrogen sulfide (H2S) synthetase inhibitor, was used to examine the effects of alli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…13 It has been shown to protect against I/R injury in various organs, including the myocardium, kidney, and brain. [14][15][16] Additionally, it can help alleviate liver damage in various hepatic diseases. 17,18 Hence, we hypothesized that allicin might protect against hepatic I/R injury.…”
Section: Introductionmentioning
confidence: 99%
“…13 It has been shown to protect against I/R injury in various organs, including the myocardium, kidney, and brain. [14][15][16] Additionally, it can help alleviate liver damage in various hepatic diseases. 17,18 Hence, we hypothesized that allicin might protect against hepatic I/R injury.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies reported that allicin improved cardiac function, and reduced the myocardial infarct area, fibrosis, degeneration, necrosis and inflammatory cell infiltration in myocardial tissue as shown in experimental models of ischemia-reperfusion injury [ 77 , 79 , 80 , 81 ]. The cardioprotection induced by allicin was mediated by restoring the levels of SOD, CAT, GPx, and MDA in the myocardial tissue of rats [ 79 ].…”
Section: Effects Of Allicin On Cardiovascular Risk Factorsmentioning
confidence: 96%
“…Other studies in MI/R in mice showed that allicin, through modulation of the miR-19a-3p/PI3K/AKT pathway, can stimulate angiogenesis and thus revascularization of infarcted areas [ 81 ]. Moreover, it has been demonstrated that allicin improved coronary vascular reactivity in MI/R in rats through the production of hydrogen sulfide (H 2 S) and the regulation of Ca 2+ homeostasis [ 80 ]. The beneficial effects of allicin on ischemia-reperfusion have been well-known and demonstrated using cell cultures as well as in vivo in experimental models.…”
Section: Effects Of Allicin On Cardiovascular Risk Factorsmentioning
confidence: 99%
“…Benzoylaconitine enhanced endothelium-dependent vasorelaxation and reduced vascular inflammation, and therefore maybe a potential modulator of the renin-angiotensin system for the treatment of hypertension. Cui et al (2022) found that allicin, an active molecular derived from garlic, exaggerated coronary artery relaxation induced by 5-hydroxytryptamine (5-HT), 9,11-dideoxy-9α,11α-methanoepoxy-prosta-5Z,13E-dien-1-oic acid (U46619), or endothelin-1 (ET-1). Allicin relaxed VSMCs via activation of the ATP-sensitive potassium (K ATP ) channels.…”
Section: Vsmcs and Vascular Dilationmentioning
confidence: 99%
“…VSMCs are the primary source of plaque cells and extracellular matrix in both early-and late-stage atherosclerosis Li et al (2022). have reviewed the effect of extracellular vesicles on VSMC in atherosclerosis.…”
mentioning
confidence: 99%